Differences in hypertension and prehypertension among people living with and without HIV in China: role of HIV infection and antiretroviral therapy. Issue 5 (9th January 2021) - Xu, X; Lin, H; Chen, X; Zhu, B; Shen, W; Ning, C; Qiao, X; Xu, X; Shi, R; Liu, X; Wong, FY; He, N; et al.
Abstract : Objectives: Hypertension is a growing health concern in people living with HIV (PLWH). However, association between HIV infection and hypertension is equivocal. Methods: In all, 1472 PLWH and 2944 HIV‐negative individuals frequency‐matched by age and sex were derived from the baseline survey of Comparative HIV and Aging Research in Taizhou (CHART), China. Prehypertension was defined as systolic blood pressure (BP) of 120–139 mmHg and/or diastolic blood pressure of 80–89 mmHg. Results: Despite the fact that prevalence of hypertension was overall lower among PLWH than among HIV‐negative people (21.1% vs . 29.1%, P < 0.001), it was similar at ages 18–29 (7.6% vs . 8.5% ) and 30–44 years (17.1% vs . 18.5%) but significantly lower in PLWH at ages 45–59 (26.1% vs . 40.7%) and 60–75 years (37.1% vs . 57.3%). Prehypertension prevalence was consistently higher in PLWH across all age groups. In the model adjusting for traditional risk factors, HIV infection was associated with hypertension (adjusted odds ratio [aOR] = 1.27, 95% confidence interval: 1.04–1.55) and prehypertension (aOR = 1.77, 95% CI: 1.51–2.08), and attenuated after additional adjustment for abdominal obesity. Age‐stratified analysis showed that these associations of HIV with hypertension were observed at ages 18–29 and 30–44 years and associations with prehypertension were observed at ages 18–29, 30–44 and 45–59 years only. Years since HIV diagnosis and stavudine use were the HIV‐specific factors independently associated with hypertension or/and prehypertension. Conclusions: HIV infection is independently associated with prehypertension and hypertension especially at younger ages, and this risk may increase as treatment becomes prolonged. Our findings reinforce the urgent necessity for active BP screening and control strategies be adopted for PLWH in China.